Highly selective magnetic affinity purification of histidine-tagged proteins by Ni2+ carrying monodisperse composite microspheres. Issue 14 (27th January 2017) - Salimi, Kouroush; Usta, Duygu Deniz; Koçer, İlkay and Çelik, Eda and Tuncel, Ali
Abstract : A magnetic sorbent based on monodisperse-porous silica microspheres was developed for His-tagged protein purification by immobilized metal affinity chromatography. Abstract : A magnetic sorbent with stable and superior magnetic behaviour was developed for His-tagged protein purification by immobilized metal affinity chromatography (IMAC). Magnetic, monodisperse and porous silica microspheres 6 μm in size, with bimodal pore size distribution including both mesoporous and macroporous compartments were synthesized as the base material by a staged-shape template hydrolysis & condensation protocol. The magnetic microspheres were functionalized with iminodiacetic acid (IDA) and Ni 2+ ions were attached onto the microspheres by metal-chelate formation via carboxyl groups. The saturation magnetization and carboxyl content of IDA attached magnetic silica microspheres were determined as 22.1 emu g −1 and 19 mmol IDA g −1 microspheres, respectively. A superior magnetic response with respect to the currently available IMAC sorbents in the form of composite magnetic nanoparticles was obtained with the proposed sorbent. The magnetic sorbent was utilized for the isolation of His-tagged green fluorescent protein (GFP) from E. coli lysate in batch-fashion. The maximum equilibrium GFP adsorption was ca. 87 mg GFP per g sorbent. GFP was isolated with high selectivity (>95% purity) and isolation yields up to 68% by changing the magnetic sorbent concentration. The superior isolation performance of the sorbent was explained by the presence of a bimodal pore structure including both macropores facilitating the intraparticular diffusion of GFP, and the mesopores serving a large surface area for parking and adsorption of GFP into the microbeads.